Out‐of‐Town Home Buyers and City Welfare - FAVILUKIS, JACK; VAN NIEUWERBURGH, STIJN (Journal of Finance, 2021)
ABSTRACT Many cities have attracted a flurry of out‐of‐town (OOT) home buyers. Such capital inflows affect house prices, rents, construction, labor income, wealth, and ultimately welfare. We develop an equilibrium model to quantify the welfare effects of OOT home buyers for the typical U.S. metropolitan area. When OOT investors buy 10% of the housing in the city center and 5% in the suburbs, welfare among residents falls by 0.61% in consumption‐equivalent units. House prices and rents rise substantially, resulting in welfare gains for owners and losses for renters. Policies that tax OOT buyers or mandate renting out vacant property mitigate welfare losses.